Comprehensive analysis of clinicopathologic and prognostic features in locally advanced thyroid papillary cancer - Liang Jiwang; Ye Dongman; Fang Fengqin; Zhao Yuejiao (Brazilian Journal of Otorhinolaryngology)
Objective: Differentiated thyroid cancers tend to excellent long-term survival after surgery. However, Locally Advanced Papillary Thyroid Cancers (LAPTCs) have poor prognosis. This study was to investigate the clinicopathologic features of LAPTC and the risk factors that affect its postoperative recurrence. We aimed to construct a nomogram to predict Recurrence-Free Survival (RFS) in LAPTC. Methods: We retrospectively reviewed the data of patients who underwent surgery from 2011 to 2020 at a single institution. Univariate and multivariate analyses were used to investigate the clinicopathologic features of LAPTC. The risk factors that affecting recurrence of LAPTC were screened. The risk factors were subsequently integrated to establish a predictive model. C-index, receiver operating characteristic curve and calibration curve were used to validate the accuracy. A Decision Analysis Curve (DCA) was used to evaluate the clinical value. Results: A total of 2530 Early Papillary Thyroid Cancer (EPTC) and 764 LAPTC were enrolled. Compared to EPTC, the proportion of male, bilaterality, multifocality, tumor size > 1 cm, ETE, central lymph node metastasis, and lateral lymph node metastasis was higher in LAPTC (all p < 0.05). Univariate and multivariate analyses found that age ≥ 55-years-old, male, and ETE were independent risk factors for the LAPTC patients’ RFS (all p < 0.05). C-index of the nomogram was 0.79. The AUC values of nomogram were 0.767 (95% CI 0.626‒0.909) and 0.798 (95% CI 0.669‒0.926) for 3- and 5-year RFS, respectively. The calibration curves of the nomogram showed good accuracy and consistency, and the DCA curves exhibited that the model had good clinical utility. Conclusion: Male patients who with tumors tumor > 1 cm, bilaterality, multifocality, and ETE are more likely to become LAPTC. LAPTC patients with age ≥ 55-years-old, tumor size > 1 cm, and ETE are more likely to have postoperative recurrence. The model can help surgeons to predict 3- and 5-year RFS in LAPTC. Evidence level: This article’s evidence level is four. Level 4 evidence, the case series, comes in the form of a group of patients subjected to surgical procedure. Authors may detect a statistically significant and clinically relevant outcome.